ANALYSIS OF THE EFFECT OF COMPETENCE, PHYSICAL ENVIRONMENT AND HUMAN RELATIONSHIP ON TEACHER PERFORMANCE ANDINTRINSIC MOTIVATION AS INTERVENING VARIABLES - Muh Habib; Kusuma Chandra Kirana; Syamsul Hadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this study is to analyze the  influence of competence, physical environment  and human relationship on teacher performance andintrinsic motivation as intervening variables. Methodology The population of this study is all teachers at SMK Ma'arif Salam Magelang, sampling  techniques using saturated samples  of 62 teachers through questionnaires,  as well as data  analysis tools using SmartPLS software Version 3.2.9.   The results showed that teacher competence has a significant influence on intrinsic motivation, physical environment  has a significant influence on intrinsic motivation, relationships have a  significant influence on   intrinsic motivation, teacher competence has a  significant influence on teacher performance, l physical environment has a significant influence on teacher performance, lphysical environment   has a significant influence on teacher performance, mintrinsic activation has a significant influence on  teacher performance.  Future research  is expected to build similar studies by adding research variables, such as handling compensation, performance appraisal systems, and others that can affect teacher performance.